Stunting and Child Development in Educational Contexts: A Socioecological Review Based on Bronfenbrenner’s Theory - Annisa Nur Rohmah; Ahmad Adin Sutariyono; Mathayo Marko Nassari (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2026)
Stunting is a multidimensional developmental condition that has long-term consequences for children’s cognitive functioning, language development, and school readiness within educational contexts. This article aims to review the impact of stunting on child development in Indonesia using Bronfenbrenner’s ecological systems theory as a socioecological framework. A systematic literature review with a narrative synthesis approach was employed. Literature searches were conducted using Google Scholar, PubMed, Scopus, SINTA, and Garuda, covering studies published between 2013 and 2026 that addressed stunting and its implications for child development and education. The findings were analyzed by categorizing evidence across ecological levels, including the microsystem, mesosystem, exosystem, and macrosystem. The synthesis reveals that stunting is associated with reduced cognitive performance by approximately 0.56-0.82 standard deviations, delayed school entry, and persistent regional disparities in educational outcomes. These effects are exacerbated by weak coordination among families, schools, health services, and policy frameworks. This review proposes a socioecological model emphasizing integrated psychoeducational interventions across sectors. The study concludes that addressing stunting requires moving beyond a nutrition-centered approach toward a holistic, education-sensitive strategy that considers children’s developmental environments in order to mitigate long-term educational disadvantages and human resource inequality in Indonesia.